The contextual method of Academician Verbitsky: is a revolution in didactics possible? - I. P. Smirnov (Russian State Vocational Pedagogical University, 2021)
Introduction. The article provides an overview of the most notable pedagogical innovations (project method, programmed teaching, pedagogy of cooperation), mastered at the scientific level, but not widely used in educational practice. Special attention is paid to the paradigm of contextual education developed by the Academician of the Russian Academy of Education, Head of the Department of Social and Pedagogical Psychology in Sholokhov Moscow State University for the Humanities, A. A. Verbitsky and his scientific school. This paradigm accumulates many effective forms, methods and means, substantiated within the framework of various innovative approaches; however, it finds application only on the experimental sites of individual creative teachers of Russia.The aim of the present publication is to investigate the reasons for the rejection by educational practice to apply pedagogical innovations, conditions and prospects.Methodology and research methods. The author analyses the works of A. A. Verbitsky's scientific school, consistently developing the paradigm of contextual education in monographic and dissertation research, mastering it in the long-term teaching practice of the leading Russian university in the field of intelligent systems in humanities and applied humanities.Results and scientific novelty. The author rejects the widespread opinion about the inhibition of innovations by the conservative pedagogical environment and shows their ideological incompatibility between the centralised management of education and the autocracy of Russian society as a whole. It is proved that the imperative of the perception of pedagogical innovations by education is a change in the social environment.Practical significance. The author's assessments and conclusions create methodological prerequisites for developing a discussion about the mission of pedagogical science and the conditions for its development in modern Russian society. Thus, it could explain why the "didactocentrism", proclaimed by John Amos Comenius, prevails in Russian education.